2009
DOI: 10.1007/bf03395652
|View full text |Cite
|
Sign up to set email alerts
|

Three Chronometric Indices of Relational Responding as Predictors of Performance on a Brief Intelligence Test: The Importance of Relational Flexibility

Abstract: Participants completed a before/after and a similar/different relational task, using the Implicit Relational Assessment Procedure (IRAP), and subsequently took the Kaufman Brief Intelligence Test (K-BIT). For each relational task, response latencies were measured first on consistent trials, where participants responded in accordance with preestablished verbal relations, and then on inconsistent trials, where they responded against these relations. A difference-score was calculated by subtracting consistent fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…The basic IRAP effect has been replicated across a number of domains in previous and ongoing research at our laboratory (Barnes-Holmes et al, 2006;Barnes-Holmes, Hayden, et al, 2008;Barnes-Holmes, Murtagh, Barnes-Holmes, & Stewart, in press;Barnes-Holmes, Waldron, Barnes-Holmes, & Stewart, in press;McKenna, Barnes-Holmes, Barnes-Holmes, & Stewart, 2007;O'Toole & Barnes-Holmes, 2009). At the current time, however, there is no published evidence to support the IRAP's validity as a potential tool for measuring clinically relevant variables.…”
mentioning
confidence: 61%
“…The basic IRAP effect has been replicated across a number of domains in previous and ongoing research at our laboratory (Barnes-Holmes et al, 2006;Barnes-Holmes, Hayden, et al, 2008;Barnes-Holmes, Murtagh, Barnes-Holmes, & Stewart, in press;Barnes-Holmes, Waldron, Barnes-Holmes, & Stewart, in press;McKenna, Barnes-Holmes, Barnes-Holmes, & Stewart, 2007;O'Toole & Barnes-Holmes, 2009). At the current time, however, there is no published evidence to support the IRAP's validity as a potential tool for measuring clinically relevant variables.…”
mentioning
confidence: 61%
“…Relational responding correlations loaded particularly highly on the Verbal Comprehension (r = .403) and Perceptual Organization (r = .409) factors of the WAIS-III. O'Toole and Barnes-Holmes (2009) employed the Implicit Relational Assessment Procedure (IRAP) to test before/after and same/ different relations and found that performance on the relational tasks that required reversing known relations correlated with IQ as measured by the Kaufman Brief Intelligence Test (r(before/after) = .38, r(same/different) = .35). Finally Gore, Barnes-Holmes, and Murphy (2010) found significant correlations between performance on a test for deictic (perspective taking) relational responding and Full Scale (r = .43), Verbal (r = .45) and Performance IQ (r = .45; p.12) as measured by the Wechsler Abbreviated Scale of Intelligence (WASI; Psychological Corporation, 1999).…”
Section: Relational Responding and Psychometric Measures Of Intelligencementioning
confidence: 99%
“…This assumption has recently received empirical support on several fronts (e.g. Gore, Barnes‐Holmes, & Murphy, ; O'Toole & Barnes‐Holmes, ) with one line of research in particular highlighting the potential of a functional approach.…”
Section: Rft Offers a Sophisticated Functional Approach To Complex Humentioning
confidence: 99%